The RESOLVE and ECO G3 Initiative: Drivers of H i Content and X-Ray Emission in Galaxy Groups - Zackary L. Hutchens; Sheila J. Kannappan; Kelley M. Hess; Andrew J. Baker; Ming Sun; Derrick S. Carr; Kathleen D. Eckert; David V. Stark (The Astrophysical Journal)
Adding to the RESOLVE and ECO Gas in Galaxy Groups (G3) initiative, we examine possible drivers of group-integrated H i -to-halo mass ratios ( M _HI,grp / M _halo ) and group X-ray emission, including group halo mass ( M _halo ), virialization as probed by crossing time ( t _cross ), presence of active galactic nuclei (AGN), and group-integrated fractional stellar mass growth rate (FSMGR _grp ). G3 groups span M _halo = 10 ^11 −10 ^14.5 M _⊙ with comprehensive H i gas and AGN information, which we combine with X-ray stacking of ROSAT All-Sky data. We detect hot gas emission exceeding AGN and X-ray binary backgrounds confidently for M _halo = 10 ^12.6 −10 ^14 M _⊙ and unambiguously for M _halo > 10 ^14 M _⊙ , reflecting an inverse dependence of M _HI,grp / M _halo and hot gas emission on halo mass. At fixed halo mass, M _HI,grp / M _halo transitions to greater spread below t _cross ∼ 2 Gyr. Dividing groups across this transition, lower- t _cross groups show elevated X-ray emission compared to higher- t _cross groups for M _halo > 10 ^13.3 M _⊙ , but this trend reverses for M _halo = 10 ^12.6 −10 ^13.3 M _⊙ . Additionally, AGN-hosting halos below M _halo ∼ 10 ^12.1 M _⊙ exhibit a broad, ∼0.25 dex deep valley in M _HI,grp / M _halo compared to non-AGN-hosting halos with correspondingly reduced FSMGR _grp . When diluted by non-AGN-hosting halos, this valley becomes shallower and narrower, falling roughly between ${M}_{{\rm{halo}}}={10}^{11.5}\,M_{\odot }$ and ${M}_{{\rm{halo}}}={10}^{12.1}\,M_{\odot }$ in the overall M _HI,grp / M _halo vs. M _halo relation. We may also detect a second, less easily interpreted valley at M _halo ∼ 10 ^13 M _⊙ . Neither valley matches theoretical predictions of a deeper valley located at or above ${M}_{{\rm{halo}}}={10}^{12.1}\,M_{\odot }$ .